Pedestrian utilization; enhancing from existing : a study case of pantai Chenang, Langkawi and Melaka Historical City, Melaka - Abd. Rahman, Abd Talip (2012)
This is a study on the pedestrian walkway, provided by local authorities. Pedestrian walkway is a crucial element in the settings of a city. Many local authorities do not see that the provision of pedestrian’s walkways without taking into account the actual requirements of users will have a negative impact on them in the future. This includes the maintenance, beautification and the provision of supporting facilities. It is therefore very important to know the profile of sites and the actual pattern of pedestrian before building a pedestrian walkway. This study will look at the extent to which existing pedestrians’ facilities were constructed without fully considering the real needs of the pedestrians flow pattern that is influenced by a variety of spatial activities in the environment. The objective of this study was to investigate the actual pattern of pedestrian flow compared with the pedestrian walkway provided by local authorities at the Pantai Chenang area and at the Melaka Historical City. Methods used in conducting this study were observational field and pedestrians count method (gate count method) to examine the utilization of the existing walkway. Findings of this study revealed that there are significant differences in pedestrian flow (for Pantai Chenang case studies) when compared with pedestrian walkways provided. The pedestrians’ concentration is influenced by the spatial activities present on site. In the case of Melaka, the difference discovered was not significant, but the concentration of pedestrians has equal criteria to the case study at Pantai Chenang. It is concentrated in areas with a variety of spatial activities. Thus, the existing spatial configuration is the important factor of the environment that affects the actual pattern of pedestrians’ flow. Time constraints and limited data are some of the challenges faced by the researchers in this study. This study will provide valuable information to local authorities in planning and designing pedestrians systems that can be fully implemented